A study in the theory of geometric functions of a complex variable - Al-Janaby, Hiba Fawzi Sabba (Institute of Engineering Mathematics, 2016)
This study aims to investigate the various results in geometric function theory. The objectives are as follows; to impose the upper and lower bounds for fractional analytic functions; to examine the various properties of a certain subclass of valent functions; to introduce new subclasses of analytic functions involving the Noor integral Operator; to apply third-order differential subordination and superordination on a new Carlson-Shaffer operator type; to investigate the connection between harmonic functions and hypergeometric functions.